Assessment of the Protective Effect of Avisure Hical against Dexamethasone-induced Osteoporosis in Wistar Rats - Thanh Tung, Tran; Phuong Thanh, Mai (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 41 No 4DO - 10.25073/2588-1132/vnumps.4818, 2025)
Abstract: Osteoporosis represents a significant public health challenge affecting millions globally. This study investigated the preventive effects of Avisure Hical capsules on osteoporosis induced by dexamethasone (Dex) compared to alendronate and calcium carbonate. Wistar rats were randomly assigned to a control group, a Dex group, and four treatment groups: one receiving alendronate (10 mg/kg body weight), another receiving CaCO 3 (27 mg/kg body weight), and two receiving Avisure Hical (0.24 and 0.48 capsules/kg body weight). Dexamethasone induced osteoporosis by reducing serum calcium (Ca), inorganic phosphorus (P), and bone mass density (BMD). Additionally, data indicated a reduction in trabecular bone quantity in the untreated Dex group. Conversely, Avisure Hical demonstrated a protective effect against Dex-induced osteoporosis by influencing the measured parameters and the histopathological structure. Our findings suggest that Avisure Hical effectively alleviates bone loss caused by dexamethasone and may serve as a promising option for preventing glucocorticoid-induced osteoporosis. Keywords: Osteoporosis, dexamethasone, Avisure Hical, rat, hydroxyapatite.